The Influence of Employee Competence and Commitment on Employee Performance with Organizational Citizenship Behavior as a Mediation Variable at PT Complus Solution System - Fitri Cahyaningrum (Return : Study of Management, Economic and Bussines, 2024)
PT Complus Sistem Solusi (PT CSS) is an information technology equipment provider in the field of system integrators and other information technology solution providers. The purpose of the study: to analyze the influence of Employee Competence and Commitment in PT CSS in an effort to improve Employee Performance by mediating Organizational Citizenship Behavior (OCB). Research method: using  the Structural Equation Modelling  method based on Partial Least Square (SEM-PLS) with the SmartPLS data processing program. The results of the study: (1) Employee competence has a significant positive effect on employee performance, (2) Employee commitment has a negative and insignificant effect on employee performance, (3) OCB has a significant positive effect on employee performance, (4) Employee competence has a significant positive effect on OCB, (5) Employee commitment has a significant positive effect on OCB, (6) Employee competence has a significant positive effect on employee performance through OCB,  (7) Employee commitment has a significant positive effect on Employee Performance through OCB.